Analisa Unjuk Kerja Heat Recovery Steam Generator Pada Blok 1 Unit 1 Pt. Indonesia Power Grati Pomu - Ferdy Wardiana, Gede; Wijaya Kusuma, I.G.B.; Sri Komaladewi, A.A.I.A. (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract PLTGU PT. Indonesia Power Grati Pomu is a power plant that uses a combination system of two systems, namely PLTG and PLTU. Where the exhaust gas from the PLTG, whose temperature still reaches 500°C, is used to produce steam. The main component used to generate steam is the Heat Recovery Steam Generator, where this component is very important to determine the input of the steam turbine whose quality and effectiveness should be prohibited. Based on these conditions, the researcher tries to analysis the performance comparison of the design and the actual HRSG or heat exchanger which must consider its effectiveness. The analysis is carried out at Block 1 Unit 1 by using the calculation of the rate of displacement, effectiveness, and pressure drop that occurs. After the assessment, the decrease in the effectiveness value, in the design condition was 23.23% and the actual condition was 13.55% with the amount of decrease that occurred was 9.68%. There is a pressure drop, for the condition in-design it reaches the value of 9149.7 Pascal and the actual condition is 9127.5 Pascal, there is a decrease of 21.46 Pascal. From the analysis conducted, it was found several factors for the implementation of decreasing the effectiveness value, namely heat rate, maximum q value, and LMTD. Keywords: Analysis, HRSG, Heat Transfer